Concentration of serum amyloid A in clinically normal endurance horses in Malaysia - Rajendren, Sujey Kumar (2015)
Endurance horses which undergo continuous strenuous training may experience injuries giving rise to inflammation which leads to an acute phase reaction with the production of acute phase protein, namely serum amyloid A (SAA). This study was conducted to establish the concentration of SAA in clinically normal endurance horses while they were rested from endurance racing. The concentration of SAA was ascertained via sampled sera from 40 individuals at three stables, using a two-site enzyme linked immunoassay (EIA) test. The highest concentration of SAA was observed in horses rested between 12 and 24 months, while horses that were rested more than 24 months expressed the lowest concentration of SAA. All horses between the ages of 6 and 11 years old had high SAA concentration. When resting intervals were compared against gender, it showed that all mares had high SAA concentration compared to geldings and stallions. Horses that were rested between 12 and 24 months may be considered prone to injuries as there may be a reduction in fitness in these horses. The SAA concentration in horses rested more than 24 months was low most probably due to the horses having recovered well from possible injuries sustained during an endurance race. SAA concentration of Thoroughbred horses were comparatively higher than Arabian horses at all rest intervals The recommended SAA reference range for the endurance horses in Malaysia is between 2.09 mg/l and 8.09 mg/l. As the endurance terrain and weather are tough in Malaysia, it is expected that the SAA concentration in endurance horses in Malaysia may be higher than other places.